Tawny, scrawny lion - Depken, Kristen L; DiCicco, Sue; Jackson, Kathryn 1907-1985 (New York Random House, 2016)
"A family of ten rabbits teaches a hungry lion to eat carrot stew--so that he won't eat them!"--
"Adapted from the beloved Little Golden Book written by Kathryn Jackson and illustrated by Gustaf Tenggren."
F&P text level G
Preschool-Kindergarten
2
Keywords: Animals -- Fiction; Lion -- Fiction; Rabbits -- Fiction